2021
DOI: 10.1029/2020jb020677
|View full text |Cite
|
Sign up to set email alerts
|

Inferring Interseismic Coupling Along the Lesser Antilles Arc: A Bayesian Approach

Abstract: An important, but originally unexpected, outcome of geodetic measurements at subduction plate boundaries over the past 20 years is that some are locked, therefore building-up elastic stresses to be released in large (M w > 7.5) megathrust earthquakes, while others appear to slip aseismically at a rate close or equal to the plate convergence rate, without generating large events. The northern Honshu subduction zone in Japan is an example of the former, with a mechanically locked plate interface and resulting el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 107 publications
3
9
0
Order By: Relevance
“…First, we observe that deep or intermediate interseismic locking of the plate interface would result in present-day uplift of the islands at rates that would be detectable by GNSS (Figure 3), whereas geodetic and micro-atoll observations both show subsidence in the 1-2 mm/yr range (Figure 2A). This is an additional argument in favor of a largely uncoupled Lesser Antilles subduction interface, consistent with the low interseismic coupling found using horizontal geodetic velocities only (van Rijsingen et al, 2021). Second, as the three locking scenarios tested here contradict the observation of present-day subsidence of the entire Lesser Antilles arc, we infer that such subsidence is not the result of seismic cycle-related processes but rather of longer-term processes, which will be discussed below.…”
Section: Vertical Gnss Confirms Uncoupled Subduction Interfacesupporting
confidence: 83%
See 2 more Smart Citations
“…First, we observe that deep or intermediate interseismic locking of the plate interface would result in present-day uplift of the islands at rates that would be detectable by GNSS (Figure 3), whereas geodetic and micro-atoll observations both show subsidence in the 1-2 mm/yr range (Figure 2A). This is an additional argument in favor of a largely uncoupled Lesser Antilles subduction interface, consistent with the low interseismic coupling found using horizontal geodetic velocities only (van Rijsingen et al, 2021). Second, as the three locking scenarios tested here contradict the observation of present-day subsidence of the entire Lesser Antilles arc, we infer that such subsidence is not the result of seismic cycle-related processes but rather of longer-term processes, which will be discussed below.…”
Section: Vertical Gnss Confirms Uncoupled Subduction Interfacesupporting
confidence: 83%
“…Two large historical earthquakes in the th century (M7-8 in 1839 and M7.5-8.5 in 1843) have been interpreted by some as thrust events, but unequivocal evidence for this is missing (e.g., Bernard and Lambert, 1988). Caribbean-wide geodetic studies over the past decade all found low interseismic coupling of the subduction interface (Manaker et al, 2008;Symithe et al, 2015), a finding recently confirmed by a more detailed study focused on the Lesser Antilles (van Rijsingen et al, 2021). Their Bayesian inversion of horizontal GNSS velocities and forward models show that the subduction interface is currently unlocked, with no re-locking of the proposed rupture areas of the 1839-1843 earthquakes.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…events, suggesting that such events either had a very low frequency or were absent during the Holocene (Paris et al 2021). Caribbeanwide geodetic studies over the past decade all found low interseismic coupling of the subduction interface (Manaker et al 2008;Symithe et al 2015), a finding recently confirmed by a more detailed study focused on the Lesser Antilles (van Rijsingen et al 2021). Their inversion of horizontal GNSS velocities and forward models show that the subduction interface is currently poorly coupled, with no re-locking of the proposed rupture areas of the 1839-1843 earthquakes.…”
mentioning
confidence: 79%
“…The GNSS data used in this study were processed as described in van Rijsingen et al (2021), with longer time-series so as to cover the 1994-2020 time interval. The vertical velocities were computed using a least-squares fit of the data with a functional form that includes a linear trend, seasonal and semi-seasonal oscillations, and step functions at times when offsets are reported (equipment change or local earthquakes) or visually detected.…”
Section: O B S E Rv E D V E Rt I C a L M O T I O N Smentioning
confidence: 99%